Analisis faktor yang mempengaruhi burnout pada tenaga kesehatan di Puskesmas Cilengkrang, Kabupaten Bandung - Tusrini, Weni; Kinanti, Sekar Nanjung; Suparni, Suparni; Ramadhan, Arfian Hikmat (PT Karya Inovasi Berkelanjutan, 2024)
Introduction Burnout has been more frequently studied among healthcare professionals such as nurses and midwives; however, limited research has focused on the broader spectrum of healthcare workers. This gap forms the basis of the present study. Unaddressed burnout conditions may negatively impact employee performance, ultimately affecting the institution. Methods This study employed a mixed-method approach using an embedded concurrent strategy. The quantitative component involved 24 respondents who completed the Maslach Burnout Inventory (MBI) questionnaire. The qualitative component included in-depth interviews with 5 primary informants and 1 key informant. Results Among the 24 healthcare workers, 8 individuals (33.3%) experienced moderate levels of burnout, while the remaining 16 (66.7%) reported low levels of burnout. Through in-depth interviews, 8 themes and 22 categories were identified, of which 12 categories were recognized as factors contributing to burnout. Conclusion and Recommendations The most influential factors contributing to burnout were workload and dual roles. Efforts to address and prevent burnout among healthcare workers are necessary, including: management evaluation of workload distribution, enhanced interpersonal approaches, development of new policies for recruiting or assigning specific personnel for administrative tasks, and improved leadership support within the organization.